Clostridioides difficile Activates Human Mucosal-Associated Invariant T Cells - Bernal, Isabel; Hofmann, Julia Danielle; Bulitta, Björn; Klawonn, Frank; Michel, Annika-Marisa; Jahn, Dieter; Neumann-Schaal, Meina; Bruder, Dunja; Jänsch, Lothar (Frontiers in Microbiology, 2018)
Clostridioides difficile infection (CDI) causes severe inflammatory responses at the intestinal mucosa but the immunological mechanisms underlying CDI-related immunopathology are still incompletely characterized. Here we identified for the first time that both, non-toxigenic strains as well as the hypervirulent ribotypes RT027 and RT023 of Clostridioides difficile (formerly Clostridium difficile), induced an effector phenotype in mucosal-associated invariant T (MAIT) cells. MAIT cells can directly respond to bacterial infections by recognizing MR1-presented metabolites derived from the riboflavin synthesis pathway constituting a novel class of antigens. We confirmed functional riboflavin synthesis of C. difficile and found fixed bacteria capable of activating primary human MAIT cells in a dose-dependent manner. C. difficile-activated MAIT cells showed an increased and MR1-dependent expression of CD69, proinflammatory IFNγ, and the lytic granule components granzyme B and perforin. Effector protein expression was accompanied by the release of lytic granules, which, in contrast to other effector functions, was mainly induced by IL-12 and IL-18. Notably, this study revealed hypervirulent C. difficile strains to be most competent in provoking MAIT cell responses suggesting MAIT cell activation to be instrumental for the immunopathology observed in C. difficile-associated colitis. In conclusion, we provide first evidence for a link between C. difficile metabolism and innate T cell-mediated immunity in humans.